2011
DOI: 10.1159/000329406
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Non-Interventional, Multi-Centre Trial of Tigecycline in the Treatment of Severely Ill Patients with Complicated Infections – New Insights into Clinical Results and Treatment Practice

Abstract: Background: Only few data are available on the efficacy of tigecycline in critically ill patients. Methods: This prospective, multicenter, non-interventional study investigated the efficacy and safety of tigecycline in hospitalized, severely ill patients with complicated intra-abdominal infections (cIAI) and/or complicated skin and soft tissue infections (cSSTI). Documentation included diagnosis, clinical findings, Acute Physiology and Chronic Health Evaluation II score, laboratory assessments, surgery, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 64 publications
(54 reference statements)
0
15
0
2
Order By: Relevance
“…Tigecycline is becoming a useful alternative against multidrug-resistant bacteria due to its broad spectrum covering both Gram-positive bacteria including methicillin-resistant Staphylococcus aureus and Gram-negative organisms except Pseudomonas aeruginosa [29,30,31]. By using the Etest method we found that 97.9% of the typed E. coli (n = 195) and 78.8% of the typed K. pneumoniae (n = 33) ESBL-producing isolates were susceptible to tigecycline, whereas a previous surveillance study performed in 2005 in Germany reported 100% of the tested ESBL-producing E. coli isolates to be susceptible to tigecycline [32].…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline is becoming a useful alternative against multidrug-resistant bacteria due to its broad spectrum covering both Gram-positive bacteria including methicillin-resistant Staphylococcus aureus and Gram-negative organisms except Pseudomonas aeruginosa [29,30,31]. By using the Etest method we found that 97.9% of the typed E. coli (n = 195) and 78.8% of the typed K. pneumoniae (n = 33) ESBL-producing isolates were susceptible to tigecycline, whereas a previous surveillance study performed in 2005 in Germany reported 100% of the tested ESBL-producing E. coli isolates to be susceptible to tigecycline [32].…”
Section: Discussionmentioning
confidence: 99%
“…MRSA is a public health problem due to its rampant spread in hospital departments and the increasing emergence of strains with reduced susceptibility to glycopeptides [6]. Previous studies of nasal carriage produced lower rates of MRSA prevalence, which may be unsurprising given the overall MRSA prevalence in the countries that were the settings of these previous investigations [7].…”
Section: Discussionmentioning
confidence: 99%
“…This study which included 1,025 patients treated in a clinical routine setting at German hospitals was initiated shortly after tigecycline was introduced in Germany. An interim analysis of a subset of patients had been previously published in this journal [32]. The current analyses of the total patient population are primarily focused on the safety profile of tigecycline and treatment modalities in these severely ill patients with complicated infections.…”
Section: Introductionmentioning
confidence: 99%